Can the children of migrant mothers have levels of health and achievement as high as children in the host population? Longitudinal data from Australia - Robinson, Julie (My University, 2014)
The high levels of immigration currently experienced by many counties in both the majority and minority worlds has seen the development and wellbeing of the children of migrants become an important social issue and field of research. However, identifying the factors that contribute to positive outcomes for children of migrants has been hampered by the widespread confounding of key variables such as parents’ migrant status, level of education, and fluency in the language of the host country. Migration to Australia offers a context in which the influence of some of these variables can be untangled because most recent migrants to Australia are highly educated and fluent in the language of the host country, regardless of their region of origin. This research uses data from the Longitudinal Study of Australian Children to compare children of migrant and Australian-born mothers at 4, 6 and 8 years of age. Most mothers were born in Australia (n=7,196), other English-speaking countries (n=788), Asia (n=576), or Europe (n=137). At each age, children’s mental and overall health (Strengths and Difficulties Questionnaire and a rating of global health), their cognitive performance (4 years: Who am I?; 6 years: matrix reasoning subscale, WISC-IV; 8 years: Academic Rating Scales) and understanding of English (Adapted Peabody Picture Vocabulary Test) were assessed. Mothers’ migration status showed little influence on their children’s outcomes at any age. For example, at 6 years, there was no main effect for maternal migration status for any outcome measure. In addition, exploratory analyses suggested that migrant mothers’ region of origin had little affect on their children’s outcomes. In contrast, the consistency and warmth of mothers’ parenting, their proficiency in English and their symptoms of depression were associated with most outcomes. The pattern of findings suggests that, in a context in which most migrants have high levels of access to social and cultural capital, their children show levels of health and achievement similar to those of the host population.
Keywords: Life Events -- Immigration / newly arrived migrants; Health; Social Capital; Education and Training -- Educational level; Health -- Mental; Disadvantage, adversity and resilience; Health and wellbeing; Learning, education and training; Education and Training; Health; Life Events; Social Capital; Immigration / newly arrived migrants; Educational level; Mental; Adversity and resilience; Learning, education and training; Health and wellbeing; Dsiadvantage, adversity and resilience